2012
DOI: 10.1126/scitranslmed.3004120
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Catheters with a Nonleaching Poly-Sulfobetaine Surface Modification Reduce Thrombus Formation and Microbial Attachment

Abstract: Adherence of proteins, cells, and microorganisms to the surface of venous catheters contributes to catheter occlusion, venous thrombosis, thrombotic embolism, and infections. These complications lengthen hospital stays and increase patient morbidity and mortality. Current technologies for inhibiting these complications are limited in duration of efficacy and may induce adverse side effects. To prevent complications over the life span of a device without using active drugs, we modified a catheter with the nonle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
199
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 43 publications
3
199
0
Order By: Relevance
“…Sulfobetaine surface coatings also have been shown to reduce thrombus formation when applied to medical grade materials in the presence of slightly reduced heparin concentrations (0.7 to 1U/mL), and clot formation on the outer surface of a sulfobetaine-coated catheter was reduced when it was inserted into a canine jugular vein in the absence of anticoagulants for 4 h, but the surface of the inner lumen was not studied 16 . Sulfobetaine surface coatings also have not been shown to withstand mechanical pumping.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfobetaine surface coatings also have been shown to reduce thrombus formation when applied to medical grade materials in the presence of slightly reduced heparin concentrations (0.7 to 1U/mL), and clot formation on the outer surface of a sulfobetaine-coated catheter was reduced when it was inserted into a canine jugular vein in the absence of anticoagulants for 4 h, but the surface of the inner lumen was not studied 16 . Sulfobetaine surface coatings also have not been shown to withstand mechanical pumping.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we successfully created antithrombogenic surfaces by applying the TLP coating to 20 different medically relevant biomaterials, whereas the sulfobetaine coating method for thrombus reduction has only been demonstrated with polyurethane 16 . Importantly, the TLP process is the first non-heparin coating to show reduced thrombogenicity in vivo on the inner lumen of tubing, which is most clinically relevant for use in extracorporeal circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group used lysozyme immobilized on polyethylene glycol monomethacrylate (PEGMA) to coat stainless steel surfaces and demonstrated that bacterial adhesion and albumin adsorption were reduced (259). Another surface modification using zwitterionic (a molecule with both positive and negative charges) nonleaching polymeric sulfobetaine (polySB) was associated with significant reductions in adherence and activation of platelets and white blood cells (260). This scaffold retains water on the surface of the catheter surface and reduces not only protein, host cell, and microbial adhesion but also thrombus formation in vitro and in vivo (260).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…OECs are considered to be a good candidate for vascular regenerating cell therapy, as they have much and sulfobetaine chemistries and are effective in resisting thrombosis 27,28) . Therefore, we developed a new stent using anti-human VE-cadherin antibody to coat ionic structures are designed to mimic phosphatidylcholine, which is abundant in cell membranes.…”
Section: Discussionmentioning
confidence: 99%